BUSINESSMAN CHIN CHUN-YEAN APPOINTED AS USM BOARD OF GOVERNORS MEMBER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 24 August 2016 - Businessman and corporate figure with extensive experience in the private sector, Chin Chun-Yean, 72, has been appointed by the Minister of Higher Education, Dato' Seri Idris Jusoh as a member of the Universiti Sains Malaysia (USM) Board of Governors, for three years beginning 1 August 2016 as a representative of the private sector.